Leishmaniose visceral no Brasil - Marcondes, Mary [UNESP]; Rossi, Claudio Nazaretian (My University, 2014)
Visceral leishmaniasis (VL) is among the most important vector-borne diseases that occur in Brazil, mainly due to its zoonotic nature. It is currently present in almost all Brazilian territory, and its control is a challenge both for veterinarians and for public health officials. Te etiologic agent is Leishmania infantum (syn chagasi), and the main vector in Brazil is Lutzomyia longipalpis. Of all animals identified as reservoirs of VL, the dog is considered the most important domestic reservoir. Although the disease has already been identified in cats, the epidemiological role of this animal species is still unclear. This article presents a brief review of the epidemiological situation of the disease, its mode of transmission, clinical features in dogs and cats as well as possible risk factors associated with the occurrence of the disease in Brazil.
Visceral leishmaniasis in Brazil
Keywords: Cats; Dogs; Epidemiology; Leishmania chagasi; Leishmania infantum